MOTIVASI MASYARAKAT INDONESIA MENJADI TENAGA KERJA INDONESIA (STUDI KASUS PADA MASYARAKAT KECAMATAN PANCENG KABUPATEN GRESIK) - Maulidyah Amalina Rizqi; Wasti Reviandani (Jurnal Manajerial, 2019)
The number of unemployed continue to rise, people can not afford to make business that is caused by bumped capital, skills, and limited market access. In fact, positive benefits for migrant workers who work abroad are also many to get jobs, income, improve welfare and develop skills. This research uses descriptive qualitative method by making the migrant workers and former migrant workers as key informant as well as to extract the data through 3 kinds of way, interview, observation and documentation. From this research, there are many factors that influence the people of Gresik Regency to become migrant workers such as, at least the employment around them, the low level of education, the economic factor of the family, and the environment, whether from the internal family and the environment. Another thing that gained from this research is still many people who become TKI with illegal status.